An Australian poet in Italy - Maver, Igor (Acta neophilologica, 2017)
The article examines the classicism of the poet A.D. Hope, especially in relation to his fascination with the work of Lord Byron, notably Childe Harold's Pilgrimage and its sections set in Italy in Rome. Hope's insistence on the European source of Australian literature in the classical antiquity found expression in several of his poems in direct intertextual references to Byron's work.
Keywords: avstralska književnost; avstralska poezija; Byron, George Gordon, 1788-1824; Hope, A. D., 1907-2000; Literarne študije